The improvement of booking process for Lea Henna / Nuruddin Ruslan - Ruslan, Nuruddin (2017)
This project is to develop a web-based system for Lea Henna with the aim to improve its booking processes. Lea Henna provides henna services as its main business. Currently booking is done manually by phone and recorded with pen and on paper that causes Lea Henna to lose customers. Many henna designs are kept in a book where they are not fully utilized. The project followed a waterfall methodology. The system was able to improve the booking process for Lea Henna with the assist of documentations which are Software Requirement Specification (SRS) and also Software Design Document (SDD).